Impact of a French social marketing campaign promoting pulse and whole grain consumption: results from a longitudinal cohort study - Fassier, Philippine; Rabès, Anaëlle; Ducrot, Pauline; Serry, Anne-Juliette (Frontiers in Nutrition, 2023)
Background: Despite the health benefits, fiber intake is insufficient among French adults. To promote the consumption of pulses and whole grains, defined as priority food groups because they are rich in fiber, readily available, and affordable, the French National Public Health Agency implemented a social marketing campaign in 2019 to improve knowledge, selfefficacy, and consumption of pulses and whole grains.Objective: To evaluate the short-and long-term effects of this social marketing campaign.Methods: A 8-month prospective study was conducted on the Internet. A sample of 4,001 French adults was interviewed before the social media campaign (T0), immediately afterwards (T1), and after 8 months (T2). Analysis was performed on 2,422 adults responding at T1 and T2. Outcomes associated with campaign recall were investigated by mixed models with random effects using generalized estimating equations.Results: Overall, 59.5% of subjects recalled the campaign. In multivariable-adjusted analyses, no significant difference was found in terms of knowledge, self-efficacy, and consumption of pulses and whole grains between those recalling and not recalling the campaign (p-value>0.05). When the analyses were stratified by educational level (p-interaction<0.10), a significant positive association was found between campaign recall and variation of knowledge about whole grain fiber content in subjects with lower educational level (p-value=0.002 at T1 and p-value=0.008 at T2). For small consumers of pulses, subjects recalling the campaign improved both their knowledge (OR [95%CI]=1.47 [1.14-1.90], p-value=0.003 at T2) and consumption of pulses (1.44 [1.14-1.86], p-value=0.002 at T1, 1.50 [1.16-1.94], p-value=0.002 at T2).Conclusion: This first French social marketing campaign promoting pulses and whole grains had a positive impact on specific subgroups of particular interest in terms of public health (i.e., people with low educational level and small consumers of pulses). These results will allow us to improve the communication materials used for the second edition of this social marketing campaign.